The Impact of Data Preprocessing on the Quality and Effectiveness of E-Learning - Rahhali, Mounia; Oughdir, Lahcen; Lahmadi, Youssef; El Khattabi, Mohammed Zakariae (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This article provides a mini review of pre-processing techniques for educational big data in data mining. With the increasing availability of educational data, there is a need for efficient pre-processing techniques that can handle the volume, variety, and velocity of data. The article discusses various pre-processing techniques, including data cleaning, data transformation, and data reduction. The review concludes that pre-processing is a critical step in data mining, and the selection of appropriate techniques depends on the characteristics of the data and the research objectives.